DEVELOPMENT OF ANIMATION-BASED MEDIA USING THE SWISHMAX APPLICATION ON OBJECT MOVEMENT MATERIALS FOR CLASS 4 STUDENTS OF STATE 25 GELUMBANG PRIMARY SCHOOL - Zulakromi; Dessy Wardiah; Aldo Pratama (SMART: Journal of Multidisciplinary Educational, 2023)
This development research aims to produce animation-based media with swishmax applicationsthat are valid and practical for grade 4 elementary schools. This study uses development researchor research and development. In this study the number of subjects was 22 students. This mediawas developed using the ADDIE model which consists of 5 stages, namely Analysis, Design,Development, Implementation, and Evaluation. Data collection was carried out with documentation, validation questionnaire sheets, and student response questionnaire sheets. thisresearch produces animation-based media with the swishmax application which is a learningmedia in the form of animated image media. The data analysis technique is carried out byanalyzing validity using a validation questionnaire sheet addressed to experts, and analyzingpracticality using a student response questionnaire. The results of data analysis of animationbased media development with the swishmax application on the material motion of objects carried out and developed by researchers are categorized as very valid from the validation questionnaire sheet with an average of 92%, animation-based media with the swishmax application on the material motion of objects developed is categorized as very practical from the aspect of teacher response with an average of 91.7% and small group questionnaire sheets in trials with an average value of 93.45%. Based on the results of validation and trials, it is concluded that this animationbased media with the swishmax application is suitable for use in the learning process.